A mulher no cinema brasileiro e a tentativa de afastamento da heteronormatividade - Calegari, Lizandro Carlos (Diálogos Latinoamericanos, 2009)
The goal of this essay is to show that the three films Dona Flor e seus dois maridos (1976), Luzia-homem (1984) and Romance da empregada (1988), while they disrupt heteronormativity, are still heavily freighted vehicles of sexual and gender ideologies. In the first case, Florípedes is a widow who marries for the second time. Sexually unsatisfied, she evokes the return of her dead husband. She transgresses heteronormativity, since society does not allow for polygamy, although she fulfills her role as a woman. In Luzia-homem, the main character acts and thinks as a man, but ends up foregoing this behavior and she takes up her destiny as a woman. In Romance da empregada, Fausta is submissive before any and all types of men, but she keeps them out of her life and remains single. In these three situations, the women attempt to mock the patriarchal code, but the plot of each film is structured in such a way that, as far as society is concerned, the women end up either repeating the roles imposed on them by patriarchal ideology or being marginalized. Such a situation reinforces a heterosexist, patriarchal, and masculinist posture.